Partisan bias in false memories for misinformation about the 2021 U.S. Capitol riot. Issue 1 (2nd January 2023) - Calvillo, Dustin P.; Harris, Justin D.; Hawkins, Whitney C.
ABSTRACT : Memory for events can be biased. For example, people tend to recall more events that support than oppose their current worldview. The present study examined partisan bias in memory for events related to the January 6, 2021, Capitol riot in the United States. Participants rated their memory for true and false events that were either favourable to their political party or the other major political party in the United States. For both true and false events, participants remembered more events that favoured their political party. Regression analyses showed that the number of false memories that participants reported was positively associated with their tendency to support conspiracy beliefs and with their self-reported engagement with the Capitol riot. These results suggest that Democrats and Republicans remember the Capitol Riot differently and that certain individual difference factors can predict the formation of false memories in this context. Misinformation played an influential role in the Capitol riot and understanding differences in memory for this event is beneficial to avoiding similar tragedies in the future.